E-171 Low glasgow coma score in traumatic intracranial hemorrhage predicts development of cerebral vasospasm. (22nd July 2018) - Al-Mufti, F; Amuluru, K; Majmundar, N; Lander, M; Matthew, M; El-Ghanem, M; Nuoman, R; Park, S; Patel, V; Gandhi, C
Abstract : Background: The exact mechanism, incidence and risk factors for cerebral vasospasm following traumatic intracranial hemorrhage (ICH) continues to be poorly characterized. The incidence of post-traumatic vasospasm (PTV) varies depending on the detection modality. Objective: We aimed to shed light on the predictors, associations and true incidence of cerebral vasospasm following traumatic ICH using digital subtraction angiography (DSA) as the gold standard. Methods: We examined a prospectively maintained database of traumatic brain injury (TBI) patients to identify patients with ICH secondary to TBI enrolled between 2002 and 2015 at our trauma center. Patients with TBI-associated ICH and evidence of vasospasm confirmed with digital subtraction angiography (DSA) were included. The diagnostic cerebral angiograms were evaluated by 2 blinded neurointerventionalists for cerebral vasospasm. Statistical analyses were conducted to determine predictors of PTV. Results: 20 patients with ICH secondary to TBI and evidence of vasospasm underwent DSAs. Seven patients (7/20; 35%) with traumatic ICH developed cerebral vasospasm and of those, one developed delayed cerebral ischemia (DCI) (1/7; 14%). Of these 7 patients, 6 presented with subarachnoid hemorrhage (SAH) (6/7; 85%). Vasospasm was substantially more common in patients with a Glasgow Coma Scale (GCS)<9 (p=0.017) than in all other groups. Conclusions: PTV as demonstrated by DCA may be more common than previously reported. Patients who exhibit PTV were more likely to have a GCS<9. This subgroup of patients may benefit from more systematic screening for the development of PTV, and earlier monitoring for signs of DCI. Disclosures: F. Al-Mufti: None. K. Amuluru: None. N. Majmundar: None. M. Lander: None. M. Matthew: None. M. El-Ghanem: None. R. Nuoman: None. S. Park: None. V. Patel: None. C. Gandhi: None.